ON DETERMINING THE SILICA IN MAGMATIC ROCKS UNDER BOREHOLE CONDITIONS BY NUCLEAR GEOPHYSICAL METHODS - Bakhterev V.V.; Ryzhiy B.P. (My University, 1990)
In studying rocks and complexes of rocks by geophysical methods, it is important to obtain information on the main groups to which the rocks belong. The successes of electric well logging in sedimentary sections, for example, are due to the fact that the knowledge of their basic characteristics correlates well with the extent of dispersion of their material. The basic criterion for classifying magmatic rocks and their effusive analogs is the silica content. Nevertheless a practically applicable method of determining SiO2 contents from logging data has not yet been developed. Yet methods of indirectly determining certain chemical elements by their relation to the nuclear-physical characteristics of the medium are known. Among these, the length of retardation of fast neutrons is one of the main integral parameters. A correlation has been established between the retardation length and the SiO2 concentrations in the rocks. Analysis of the potential for this method of determining the retardation length and the experimentally obtained results leads to the conclusion that the correlation between the retardation length and the SiO2 content holds for rock bodies with the same degree of fracturing and the same water content. If the degree of fracturing and the water content of the rocks vary, the retardation length will depend essentially on the water content.